Stromal Targets for Fluorescent-Guided Oncologic Surgery - Boonstra, Martin C.; Prakash, Jai; Van De Velde, Cornelis J. H.; Mesker, Wilma E.; Kuppen, Peter J. K.; Vahrmeijer, Alexander L.; Sier, Cornelis F. M. (Frontiers in Oncology, 2015)
Pre-operative imaging techniques are essential for tumor detection and diagnosis, but offer limited help during surgery. Recently the applicability of imaging during oncologic surgery has been recognized, using near infrared fluorescent dyes conjugated to targeting antibodies, peptides or other vehicles. Image-guided oncologic surgery (IGOS) assists the surgeon to distinguish tumor from normal tissue during operation, and can aid in recognizing vital structures. IGOS relies on an optimized combination of a dedicated fluorescent camera system and specific probes for targeting. IGOS probes for clinical use are not widely available yet, but numerous pre-clinical studies have been published and clinical trials are being established or prepared. Most of the investigated probes are based on antibodies or peptides against proteins on the membranes of malignant cells, whereas others are directed against stromal cells. Targeting stroma cells for IGOS has several advantages. Besides the high stromal content in more aggressive tumor types, the stroma is often primarily located at the periphery/invasive front of the tumor, which makes stromal targets particularly suited for imaging purposes. Moreover, because stroma up-regulation is a physiological reaction, most proteins to be targeted on these cells are ‘universal’ and not derived from a specific genetic variation, as is the case with many upregulated proteins on malignant cancer cells.